INTEGRATION OF THE IMMERSIVE APPROACH INTO THE EDUCATIONAL PROCESS (World Bulletin of Management and Law, 2025)
The article discusses the features of the immersive learning method and its integration into the educational process, which makes learning more interesting and engaging for the younger generation, as well as helps in their comprehensive development. This method not only immerses students in an interactive environment but also increases their interest, motivation, and quality of knowledge.
Keywords: immersive technologies; virtual and augmented reality